Robot's Impression of Appearance and Their Trustworthy and Emotion Richness - Matsui, Tetsuya; Yamada, Seiji (2018 27th IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN), 2018)
This paper focused on the appearance of humanoid robot and their trustworthy and emotion richness perceived. Humanoid robots that used in emotional labor is needed to express emotion and be trusted. We experimented with eight robots image(four mechanical face robots and four smooth face robots) and asked the participants their impression. We conducted explanatory factor analysis to define the factors of robots' impression. As a result, the factors of robots were discovered to be different from the virtual humans' impression. Also, the trustworthy and emotion richness perceived of robots depended on another factors. The familiar robots were trusted and the human-like robots were expected to have rich emotion.